Zika virus infection in pregnant women and their children: A review. (October 2021) - Marbán-Castro, Elena; Goncé, Anna; Fumadó, Victoria; Romero-Acevedo, Lucía; Bardají, Azucena
Highlights: Zika virus (ZIKV) infection in pregnancy is a cause of pregnancy loss and child neurodevelopmental impairment. Congenital Zika syndrome includes microcephaly, brain disruption, ocular anomalies, contractures, and seizures among other birth defects. Infants exposed to ZIKV in utero with no defects at birth may develop postnatal microcephaly and/or present with later neurodevelopmental impairment. Screening for ZIKV infection in exposed pregnant women is essential, as most infections are asymptomatic and clinical manifestations non-specific. The follow-up of children with prenatal exposure to ZIKV is crucial for a prompt detection of any potential neurological impairment. Abstract: Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) transmitted primarily by Aedes mosquitoes. ZIKV can be transmitted to humans by non-vector borne mechanisms such as sexual intercourse, maternal-foetal transmission or blood transfusion. In 2015, ZIKV emerged in the Americas, and spread to 87 countries and territories with autochthonous transmission, distributed across four of the six WHO regions. Most ZIKV infections in pregnancy are asymptomatic, but mother to child transmission of the virus can occur in 20 to 30% of cases and cause severe foetal and child defects. Children exposed to ZIKV while in utero might develop a pattern of structural anomalies and functional disabilities secondary to central nervous system damage, known as congenital Zika syndrome, and whose most common clinical feature is microcephaly. Normocephalic children born to mothers with ZIKV infection in pregnancy, and with no observable Zika-associated birth defects, may also present with later neurodevelopmental delay or post-natal microcephaly. Screening and detection of ZIKV infection in pregnancy is essential, because most women with ZIKV infection are asymptomatic and clinical manifestations are non-specific. However, the diagnosis of ZIKV infection poses multiple challenges due to limited resources and scarce laboratory capabilities in most affected areas, the narrow window of time that the virus persists in the bloodstream, the large proportion of asymptomatic infections, and the cross-reactivity with other flaviviruses such as Dengue virus (DENV). Molecular methods (RT-PCR) are the most reliable tool to confirm ZIKV infection, as serodiagnosis requires confirmation with neutralization tests in case of inconclusive or positive serology results. Prenatal ultrasound assessment is essential for monitoring foetal development and early detection of possible severe anomalies. A mid- and long-term follow-up of children exposed to ZIKV while in utero is necessary to promptly detect clinical manifestations of possible neurological impairment. Tweetable abstract: Zika virus infection during pregnancy is a cause of pregnancy loss and disability in children. Protection against mosquito bites, access to sexual and reproductive health services, prompt screening and detection of ZIKV infection in pregnancy, and prenatal ultrasound monitoring are key control strategies whilst a vaccine is not available.